Defining moments : historic decisions by Arkansas governors from McMath through Huckabee - Brown, Robert L., 1941- (University of Arkansas Press, 2010)
Robert L. Brown is an Arkansas Supreme Court justice and has been involved with Arkansas politics for over forty years.